(untitled) (Research, Society and Development, 2022)
Disorganized growth creates social disparities, in addition to degradation in natural and artificial systems. These problems are attenuated with urban development, preventing a city from being sustainable, reducing the quality of life, there will be no social equity, as well as increased pollution and violence rates, to achieve sustainability a municipality must be equipped with data and information that detects points to be improved in development, in view of this situation, this article aimed to carry out a sustainability ranking with indexes that represent the urban reality of Pará municipalities, and to analyze each location individually. The analyzed Pará municipalities need to outline strategies for improving urban sustainability, as they did not present good results when analyzed individually in the social, mobility and accessibility, economic and social parameters.